Photoacoustic Effect of Near-Infrared Absorbing Organic Molecules via Click Chemistry - Wenqing Zhu; Zongcheng Miao; Yaqin Chu; Liaoliao Li; Lei Wang; Dong Wang (Molecules, 2022)
Near-infrared dyes were developed to be contrast agents due to their ability to improve the productivity of photoacoustic (PA) imaging and photothermal therapy (PTT) treatments. During the article, we described in detail the PA and PT effects of a category of organic molecules. F4-TCNQ could potentially cause a red-shift in the peak PA intensity. The results show that the PTT intensity of the near-infrared dyes with phenyl groups were higher than near-infrared dyes with thiophene groups. We also investigated the photodynamic treatment effect of C1b to demonstrate that these dyes are highly desirable in biochemistry. The high photoacoustic intensity of the organic molecules and the good yield of reactive oxygen species could indicate that these dyes have good potential for a wide range of imaging applications. Finally, we embedded the dye (C1b) in a liposomal hydrophobic phospholipid bilayer (C1b⊂L) to facilitate the application of hydrophobic dyes in biomedical applications, which can be absorbed by cells with good compatible and high stability for the imaging of cellular PA.